Existencillism: Banksy and the stencil as radical graphic form. Issue 1 (1st January 2016) - Gough, Paul
Contemporary graffiti artists, or 'writers' as they are known, observe a strict hierarchy that self-ranks ambition, daring and calligraphic innovation. At the apex are those writers who create the imposing wildstyle exhibition pieces, large-scale vivid inscriptions that require a high degree of graphic invention and daring. At the other extreme are the stencil-cutters, who by comparison are regarded within the peer community of the subculture, as lesser writers, relying on craft skills that are held to be quaint, even fraudulent. This article explores the persistence and ubiquitous spread of the stencil as a vehicle for mass-produced street art, made especially popular through the iconic work of British street-artist Banksy. Exploring the origins of his work in stencil the article examines how he has both radicalized the genre, while still retaining its essential value as an industrial, utilitarian and iconic graphic. The article compares the deadpan, but hugely popular, drawn language of the stencil with the freehand calligraphy of the taggers, 'kings' and other exhibition 'writers', and closes with a set of questions, in particular: what is the future of drawing in countercultural expression?